Precarious Employment and Difficult Daily Commutes - Premji, Stéphanie (Relations industrielles / Industrial Relations, 2017)
Precarious employment is on the rise in Canada, increasing by nearly 50% in the last two decades. However, little is known about the mechanisms by which it can impact upon geographical mobility. Employment-related geographical mobility refers to mobility to, from and between workplaces, as well as mobility as part of work. We report on a qualitative study conducted among 27 immigrant men and women in Toronto that investigates the relationship between precarious employment and daily commutes while exploring the ways in which gender, class and migration structure this relationship.Interview data reveal that participants were largely unable to work where they lived or live where they worked. Their precarious jobs were characterized by conditions that resulted in long, complex, unfamiliar, unsafe and expensive commutes. These commuting difficulties, in turn, resulted in participants having to refuse or quit jobs, including desirable jobs, or being unable to engage in labour market strategies that could improve their employment conditions (e.g. taking courses, volunteering, etc.). Participants’ commuting difficulties were amplified by the delays, infrequency, unavailability and high cost of public transportation. These dynamics disproportionately and/or differentially impacted certain groups of workers.Precarious work has led to workers having to absorb an ever-growing share of the costs associated with their employment, underscored in our study as time, effort and money spent travelling to and from work. We discuss the forces that underlie the spatial patterning of work and workers in Toronto, namely the growing income gap and the increased polarization among neighbourhoods that has resulted in low-income immigrants increasingly moving from the centre to the edges of the city. We propose policy recommendations for public transportation, employment, housing and child care that can help alleviate some of the difficulties described.